2018
DOI: 10.1097/pec.0000000000000782
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Return Visits to the Pediatric Emergency Department

Abstract: The most commonly reported reasons for pediatric return visits were continued symptoms and lack of illness understanding. We plan to use these data to develop targeted interventions to decrease the perceived need for return visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
39
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 18 publications
3
39
1
Order By: Relevance
“…However, another study reported that 94% of returned caregivers were satisfied with the first ED physician encounter . A recent study reported that caregivers of children who were admitted on the return visit were more dissatisfied with care at the first visit than caregivers of children who were discharged on the return visit . Our study shows different results; we found similar scores between patients who were discharged on the return visit and patients who were hospitalized in all PSQ items (Table ).…”
Section: Discussioncontrasting
confidence: 58%
See 4 more Smart Citations
“…However, another study reported that 94% of returned caregivers were satisfied with the first ED physician encounter . A recent study reported that caregivers of children who were admitted on the return visit were more dissatisfied with care at the first visit than caregivers of children who were discharged on the return visit . Our study shows different results; we found similar scores between patients who were discharged on the return visit and patients who were hospitalized in all PSQ items (Table ).…”
Section: Discussioncontrasting
confidence: 58%
“…These unanticipated revisits are stressful for patients and parents; they increase overcrowding and health‐care costs, and add to the already high workload of ED staff . The most commonly reported reasons for ED revisits are continued symptoms, natural progression of illness, lack of understanding of illness, lack of follow‐up plans, and lack of personalized discharge instructions …”
mentioning
confidence: 99%
See 3 more Smart Citations